Revitalization of Village-Owned Enterprises to Strengthen the Community Economy in Indonesia: Between Policy and Prosperity - Satoto, Sukamto; Nuriyatman, Eko; Mushawirya, Rustian; Mujib, M. Misbahul; Haq, Muhammad Izzul (Jambe Law Journal, 2024)
Indonesian president-elect, Prabowo Subianto, has emphasized his vision through Astacita, continuing President Joko Widodo’s Nawacita concept. The primary focus is on village development and community economic empowerment to reduce inequality and poverty. This study employs a qualitative descriptive approach, analyzing legal data, regulations, and philosophical, political, and economic perspectives related to Village-Owned Enterprises (BUMDes). The main objective is to explore the urgency of revitalizing BUMDes to encourage village development, improve the local economy, and align with policies aimed at fostering community-based welfare.  The Village Law strengthens the role of villages in development, with BUMDes acting as a key driver of the village economy. However, BUMDes faces challenges in management and competitiveness. To address this, revitalization and collaboration are necessary to increase productivity, leverage local potential, and support community welfare. The government must enhance policies, improve management capacity, and protect BUMDes from harmful competition. Digitalization and synergy between villages also present solutions to bolster the village economy in the Industry 4.0 era.  BUMDes plays a crucial role in boosting the village economy based on local potential, but participatory, transparent, and professional management is essential for its independent development. Strengthening subsidiarity and village authority accelerates sustainable development, in line with global trends in enhancing local governance and village economic autonomy. The revitalization of BUMDes is a key strategy for improving the village economy through the optimization of village funds and digitalization. Addressing management challenges requires enhanced capacity for village officials, strict supervision, and inclusive policies to foster sustainable economic growth and community welfare